2001
DOI: 10.1016/s0031-9406(05)60696-7
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Different Methods for Assessing Standing Balance

Abstract: This paper is a review of the balance assessment methods currently used to evaluate standing balance. Most of the presently available instrumentation appears to be more suited to research laboratories than to routine clinical situations. Functional assessments of balance appear to be the quickest test to administer and do not require expensive equipment however only gross changes in balance can be detected making them suitable as a screening tool for identifying subject's needing more thorough evaluation. Forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 31 publications
(27 reference statements)
1
49
0
Order By: Relevance
“…Sonometric measurements revealed that, despite the fact that the study participants were performing a standard midwifery activity, their spatial spinal configuration might distinctively vary among midwives both with reference to the location and to the body plane in which the most unergonomic spine arrangement was recognized. It is due to individual-specific spinal flexibility and habitual movement patterns [10,11]. Multisegmental and multiplane spine movement abilities present favorable conditions for compensatory movements of body segments which secure body stability.…”
Section: Resultsmentioning
confidence: 99%
“…Sonometric measurements revealed that, despite the fact that the study participants were performing a standard midwifery activity, their spatial spinal configuration might distinctively vary among midwives both with reference to the location and to the body plane in which the most unergonomic spine arrangement was recognized. It is due to individual-specific spinal flexibility and habitual movement patterns [10,11]. Multisegmental and multiplane spine movement abilities present favorable conditions for compensatory movements of body segments which secure body stability.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that when compared with inexperienced controls, experienced HHS wearers showed more conservative and stable body control during single-limb support, but a fast weight transfer during double-limb support. However, the effect of HHS wearing experience on human balance in terms of standing balance and functional mobility remains largely unknown, even though both standing balance and functional mobility are critical components of a person's ability to perform daily activities and have been widely used in assessing human balance and the risk of falling (Winter 1995;Tang, Moore, and Woollacott 1998;Arnadottir and Mercer 2000;Browne and O'Hare 2001;Wallmann 2001;Garland et al 2003;Mancini and Horak 2010;Kasser et al 2011;Gerber et al 2012). A c c e p t e d M a n u s c r i p t Therefore, the objective of this study is two-fold.…”
Section: Introductionmentioning
confidence: 99%
“…[23] The state of the patient in the sitting/standing position was monitored daily whereas the core was calculated and interpreted according to the scale. [24] -the Fugl-Meyer scale for the evaluation of the different sensitivity disorders in the sick lower limbs. [23] The exercise program enables the functional recovery and also the development of the social, professional, psychical and communicative functions.…”
Section: Methodsmentioning
confidence: 99%